Painless self-mutilation − A case of hereditary sensory autonomic neuropathy type 4 - Prateek Pathak; Mohammad Adil; Syed Suhail Amin; Fatima Tuz Zahra (Wolters Kluwer Medknow Publications, 2022)
Children with hereditary sensory and autonomic neuropathy (HSAN) Type IV present with loss of pain and temperature sensation and anhidrosis. They may sometimes exhibit aggressive and self-mutilating behavior. We present here the case of a 5-year-old male child who presented with a history of self-mutilating behavior leading to ulcers over knees, elbows, toes and occiput, and amputation of index fingers of both hands. The patient had loss of temperature and pain sensation, but touch was normal. There was anhidrosis. Serum uric acid levels were normal. Histamine test was absent, and nerve studies showed decreased conduction velocity. A diagnosis of HSAN Type IV was made. This case is being presented as self-mutilation was the prominent complaint of the parents of the child. We also discuss the differences between HSAN Type IV and Lesch−Nyhan syndrome.